2005
DOI: 10.1111/j.1747-0765.2005.tb00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Soybean-Nodulating Rhizobia Isolated from Alkaline Soils in Vietnam

Abstract: In order to analyze the phylogeny of soybean-nodulating bacteria in alkaline soils in Vietnam, indigenous soybean-nodulating bacteria were isolated from root nodules by cultivating three kinds of &j-soybean cultivam on two alkaline soils in Vietnam. The 120 isolates were classified into two major genera of soybean-nodulating rhizobia, namely Brudyrhizobium and Sinorhizobium genera, based on a growth analysis on medium and PCR-RFLP analyses of 16s rDNA and of the 165-23s rDNA internal transcribed spacer (ITS) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 27 publications
3
55
0
Order By: Relevance
“…Saeki et al [5] reported that Rj gene soybean cultivars affect compatibility and preference for nodule formation between the host cultivar and rhizobial bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Saeki et al [5] reported that Rj gene soybean cultivars affect compatibility and preference for nodule formation between the host cultivar and rhizobial bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Direct sequencing was carried out by using the PCR products as templates and the PCR primers with an ABI PRISM 310 DNA sequencer and Big Dye Terminator v.3.1 Cycle Sequencing Kit (Applied Biosystems, Foster City, CA, USA). PCR amplification and sequence analysis of 16S-23S rDNA ITS sequences were performed as described by Saeki et al (2005Saeki et al ( , 2006. Table 1 lists the DDBJ/GenBank/EMBL accession numbers for the 16S rRNA genes and ITS sequences between 16S-and 23S-rRNA that are used in this study.…”
Section: Comparative Genomic Hybridizationmentioning
confidence: 99%
“…As soybean-nodulating sinorhizobia will inhabit alkaline soils exclusively (Saeki et al, 2005;Suzuki et al, 2008), and because the soils sampled in this study were all acidic, it is reasonable to assume that all isolates in the present study belonged to genus Bradyrhizobium, and that most were B. japonicum, as suggested by the soybean root nodulation, alkaline production on YMA medium, and the PCR-RFLP analysis results. Bradyrhizobial community diversities, determined by pair-wise comparison, among soybean cultivars of each Rj genotype are shown in Table 4 and Fig.…”
Section: Diversity Among Rhizobial Communities Within Identical or DImentioning
confidence: 93%
“…Specific rhizobial strains can be incompatible with soybean cultivars harboring a particular Rj gene. In addition, indigenous soybean-nodulating rhizobia may show a preference for particular genotypes among the compatible genotypes, even among soybean plants cultivated in soil samples from the same field (Ishizuka et al, 1991;Saeki et al, 2000Saeki et al, , 2005. It is therefore important to use soybean cultivars with different Rj genotypes for both isolating and analyzing indigenous soybean-nodulating rhizobia.…”
Section: Grouping Of Indigenous Bradyrhizobia In Japanmentioning
confidence: 99%
See 1 more Smart Citation